Kreativitas Manajerial Kepala Sekolah dalam Meningkatkan Mutu Pembelajaran di Yayasan Buddhist Manjusri Kota Pematangsiantar - Darwin Darwin; Aulia Christina Sinaga; Enjel Oktaviany Simanjuntak; Rosvina Sari Siburian (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
This study aims to describe the managerial creativity of school principals in improving the quality of learning at the Buddhist Foundation. The leadership of the principal greatly determines the progress of a school. The research used is descriptive qualitative research. Qualitative research methods are research methods to explore and understand the meaning that according to some individuals or groups of people comes from social or human problems. The results showed that maturity in mastering the theories and concepts of management and leadership requires integrated and continuous training and training. The content of the learning curriculum requires weighting on the theory and implementation of organizational management and leadership. That the success of education through the application of management in schools requires principals who have high managerial and professional integrity and democratic abilities in the decision-making process, especially regarding the managerial creativity of school principals.